흑미 수확시기에 따른 이화학적 특성 및 항산화 활성 변화 - 박지영(Ji-Young Park); 한상익(Sang-Ik Han); 허연재(Yeon-jae Hur); 이유영(Yu-Young Lee); 이병원(Byung-Won Lee); 심은영(Eun-Yeong Sim); 함현미(Hyeonmi Ham); 김병주(Byeong-Ju Kim); 이춘우(Chun-Woo Lee); 이성준(Sung-Joon Lee); 오성환(Sung-Hwan Oh) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2015)
This study compared physicochemical properties and antioxidant activities according to different harvest times in five varieties of black rice (BR). Five cultivars of BR, Nunkeunheukchal (NKHC), Sinnongheugchal (SNHC), Sintoheugmi (STHM), Josaengheugchal (JSHC), and Heugjinju (HJJ), were selected for the study. Cultivars were transplanted on June 20th and cultivated by the Department of Southern Area Crop Science, NICS in Miryang, Korea. Heading dates of NKHC, SNHC, STHM, JSHC, and HJJ were Aug. 17th, Aug. 30th, Sep. 1st, Aug. 20th, and Aug. 12th, respectively. The five different harvest times were as follows; 35, 40, 45, 50, and 55 days after heading date. The highest level of anthocyanin was 35 days after heading date in all varieties. Levels of anthocyanin in NKHC, SNHC, STHM, JSHC, and HJJ were 164, 203, 251, 67, and 210 mg/100 g, respectively. Content of anthocyanin significantly decreased 35 days after heading in four varieties, excluding JSHC. Highest DPPH $IC_{50}$ values were 57, 29, 10, and $27μg/mL$ in NKHC, SN HC, STHM, and JSHC extracts, respectively. Highest ABTS $IC_{50}$ values were 24, 13, 9, and $11μg/mL$ in NKHC, SNHC, STHM, and JSHC extracts, respectively. The antioxidant activities were highest 35 days after the heading date and significantly decreased in four varieties, excluding HJJ. The antioxidant activity of HJJ showed no significant difference, according to harvest time. This study suggests that the content of anthocyanin and antioxidant activity could be considered as factors affecting optimal harvest period to produce highly qualified black rice. 본 연구는 흑미 수확시기에 따른 종실의 이화학적 특성 및 항산화 활성 변이를 검토하였는데, 실험에 이용된 흑미 5개 품종(눈큰흑찰, 신농흑찰, 신토흑미, 조생흑찰, 흑진주)의 출수일로부터 각각 35, 40, 45, 50, 55일에 수확을 하여 출수 후 수확일수에 따른 특성을 비교한 결과, 무기성분(칼륨, 칼슘, 마그네슘)은 수확시기에 따른 유의성이 인정되지 않았다. 기능성 성분인 폴리페놀의 경우 흑진주를 제외하고 4개 품종에서 출수 후 35일 이후 시간이 지날수록 감소하는 경향이었고, 플라보노이드도 조생흑찰 및 흑진주를 제외하고 수확시기에 따라 함량이 감소하는 경향이었다. 수확시기와 안토시아닌 함량과의 관계를 분석한 결과 모든 품종이 부의 상관관계를 보였고, 흑진주벼를 제외하고는 $R^2$ 값이 0.8~0.9 정도로 유의성이 인정되었다. 항산화 활성 또한 흑진주 벼를 제외하고는 출수 후 35일경이 항산화 활성이 가장 높았고, 이후 점점 감소하는 경향이었다.